Effects of the Angiotensin‐Receptor Neprilysin Inhibitor on Cardiac Reverse Remodeling: Meta‐Analysis. Issue 13 (2nd July 2019) - Wang, Yiwen; Zhou, Ran; Lu, Chi; Chen, Qing; Xu, Tongda; Li, Dongye
Abstract : Background: The angiotensin‐receptor neprilysin inhibitor (ARNI) sacubitril/valsartan was shown to be superior to the angiotensin‐converting enzyme inhibitor enalapril in terms of reducing cardiovascular mortality in the PARADIGM‐HF (Prospective Comparison of ARNI with angiotensin‐converting enzyme inhibitor to Determine Impact on Global Mortality and Morbidity in Heart Failure) study. However, the impact of ARNI on cardiac reverse remodeling (CRR) has not been established. Methods and Results: We conducted a meta‐analysis to compare the effects of ARNI versus angiotensin‐converting enzyme inhibitors or angiotensin receptor blockers on CRR indices. We searched databases for studies published between 2010 and 2019 that reported CRR indices following ARNI administration. Effect size was expressed as mean difference (MD) with 95% CIs. Twenty studies enrolling 10 175 patients were included. ARNI improved functional capacity in patients with heart failure (HF) and a reduced ejection fraction (EF), including increasing New York Heart Association functional class (MD −0.79, 95% CI −0.86, −0.71) and 6‐minute walking distance (MD 27.62 m, 95% CI 15.76, 39.48). ARNI outperformed angiotensin‐converting enzyme inhibitors/angiotensin receptor blockers in terms of CRR indices, with striking changes in left ventricular EF, diameter, and volume. However, there were no significant improvements in indices except left ventricular mass index (MD −3.25 g/m 2, 95% CI −3.78, −2.72) and left atrial volume (MD −7.20 mL, 95% CI −14.11, −0.29) in HF patients with preserved EF treated with ARNI. Improvements in CRR indices were observed at 3 months and became more significant with longer follow‐up to 12 months. The regression equation for the relationship between left ventricular EF and end‐diastolic dimension was y=0.041+0.071x+0.045x 2 +0.006x 3 . Conclusions: ARNI distinctly improved left ventricular size and hypertrophy compared with angiotensin‐converting enzyme inhibitors/angiotensin receptor blockers in HF with reduced EF patients, even after short‐term follow‐up. Patients appeared to benefit more in terms of CRR treated with ARNI as early as possible and for at least 3 months. Further large sample trials are required to determine the effects of ARNI on CRR in HF with preserved EF patients.